2023
DOI: 10.3389/fendo.2023.1115834
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between thyroid dysfunction and hallux valgus: A two-sample Mendelian randomization study

Abstract: IntroductionPrevious observational studies have reported that thyroid dysfunction is associated with hallux valgus (HV). However, the causal effect of thyroid dysfunction on hallux valgus is still unknown. To assess whether there is a causal relationship between thyroid dysfunction and hallux valgus, we performed a two-sample Mendelian randomization (MR) study.MethodsThe data of the two-sample Mendelian randomization study were obtained from public databases. In this study, hypothyroidism, hyperthyroidism, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Our previous research indicated a significant correlation between low HGS and an increased risk of all‐cause mortality and cardiovascular mortality in the American population 7 . Furthermore, we have identified a causal relationship between HGS and all‐cause mortality based on a Genome‐wide association study analysis of a population of 1.1 million Europeans 8 . Additionally, HGS serves as a predictor of hip fracture recovery and is associated with falls and fractures in older adults 9,10 .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our previous research indicated a significant correlation between low HGS and an increased risk of all‐cause mortality and cardiovascular mortality in the American population 7 . Furthermore, we have identified a causal relationship between HGS and all‐cause mortality based on a Genome‐wide association study analysis of a population of 1.1 million Europeans 8 . Additionally, HGS serves as a predictor of hip fracture recovery and is associated with falls and fractures in older adults 9,10 .…”
Section: Introductionmentioning
confidence: 86%
“…7 Furthermore, we have identified a causal relationship between HGS and allcause mortality based on a Genome-wide association study analysis of a population of 1.1 million Europeans. 8 Additionally, HGS serves as a predictor of hip fracture recovery and is associated with falls and fractures in older adults. 9,10 Dowling et al found that reduced muscle strength in elderly women with obesity in the UK significantly increases the risk of falls and fractures, particularly in the lower extremities.…”
Section: Introductionmentioning
confidence: 99%